Two distant helicases in one mycovirus: evidence of horizontal gene transfer between mycoviruses, coronaviruses and other nidoviruses. Issue 1 (1st May 2021) - Abdoulaye, Assane Hamidou; Hai, Du; Tang, Qing; Jiang, Daohong; Fu, Yanping; Cheng, Jiasen; Lin, Yang; Li, Bo; Kotta-Loizou, Ioly; Xie, Jiatao
Abstract: Nidovirales, which accommodates viruses with the largest RNA genomes, includes the notorious coronaviruses; however, the evolutionary route for nidoviruses is not well understood. We have characterized a positive-sense (+) single-stranded (ss) RNA mycovirus, R hizoctonia s olani h ypov irus 2 (RsHV2), from the phytopathogenic fungus Rhizoctonia solani . RsHV2 has the largest RNA genome size of 22, 219 nucleotides, excluding the poly(A) tail, in all known mycoviruses, and contains two open reading frames (ORF1 and ORF2). ORF1 encodes a protein of 2, 009 amino acid (aa) that includes a conserved helicase domain belonging to helicase superfamily I (SFI). In contrast, ORF2 encodes a polyprotein of 4459 aa containing the hallmark genes of hypoviruses. The latter includes a helicase belonging to SFII. Following phylogenetic analysis, the ORF1-encoded helicase (Hel1) unexpectedly clustered in an independent evolutionary branch together with nidovirus helicases, including coronaviruses, and bacteria helicases. Thus, Hel1 presence indicates the occurrence of horizontal gene transfer between viruses and bacteria. These findings also suggest that RsHV2 is most likely a recombinant arising between hypoviruses and nidoviruses.